Application Potential of Baijiu Non-Saccharomyces Yeast in Winemaking Through Sequential Fermentation With Saccharomyces cerevisiae - Li, Rui-Rui; Xu, Meng; Zheng, Jia; Liu, Yan-Jun; Sun, Chun-Hong; Wang, Huan; Guo, Xue-Wu; Xiao, Dong-Guang; Wu, Xiao-Le; Chen, Ye-Fu (Frontiers in Microbiology, 2022)
To explore the potential application of non-Saccharomyces yeasts screened from Baijiu fermentation environment in winemaking, the effect of four Baijiu non-Saccharomyces yeasts (two Zygosaccharomyces bailii and two Pichia kudriavzevii) sequentially fermented with Saccharomyces cerevisiae on the physicochemical parameters and volatile compounds of wine was analyzed. The results indicated that there was no obvious antagonism between S. cerevisiae and Z. bailli or P. kudriavzevii in sequential fermentations, and all strains could be detected at the end of alcoholic fermentation. Compare with S. cerevisiae pure fermentation, Z. bailii/S. cerevisiae sequential fermentations significantly reduced higher alcohols, fatty acids, and ethyl esters and increased acetate esters; P. kudriavzevii/S. cerevisiae sequential fermentations reduced the contents of C6 alcohols, total higher alcohols, fatty acids, and ethyl esters and significantly increased the contents of acetate esters (especially ethyl acetate and isoamyl acetate). Sequential fermentation of Baijiu non-Saccharomyces yeast and S. cerevisiae improved the flavor and quality of wine due to the higher ester content and lower concentration of higher alcohols and fatty acids, non-Saccharomyces yeasts selected from Baijiu fermentation environment have potential applications in winemaking, which could provide a new strategy to improve wine flavor and quality.